2018
DOI: 10.1002/cssc.201800610
|View full text |Cite
|
Sign up to set email alerts
|

CH3NH3PbI3 and HC(NH2)2PbI3 Powders Synthesized from Low‐Grade PbI2: Single Precursor for High‐Efficiency Perovskite Solar Cells

Abstract: High-efficiency perovskite solar cells are generally fabricated by using highly pure (>99.99 %) PbI mixed with an organic iodide in polar aprotic solvents. However, the use of such an expensive chemical may impede progress toward large-scale industrial applications. Here, we report on the synthesis of perovskite powders by using inexpensive low-grade (99 %) PbI and on the photovoltaic performance of perovskite solar cells prepared from a powder-based single precursor. Pure APbI [A=methylammonium (MA) or formam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 58 publications
(94 reference statements)
0
59
0
Order By: Relevance
“…The presence of the pinholes may result in subsequently coated HTM solutions to deleteriously infiltrate into the perovskite absorber layer. It increased the recombination of electron and hole due to the large contact area between HTM and perovskite [ 13 ]. Furthermore, for NAA and NHA solvents, some nanorods/nanoplates were observed to grow on the film surface, which will be detrimental to the performance of the perovskite solar cell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the pinholes may result in subsequently coated HTM solutions to deleteriously infiltrate into the perovskite absorber layer. It increased the recombination of electron and hole due to the large contact area between HTM and perovskite [ 13 ]. Furthermore, for NAA and NHA solvents, some nanorods/nanoplates were observed to grow on the film surface, which will be detrimental to the performance of the perovskite solar cell.…”
Section: Resultsmentioning
confidence: 99%
“…Organic-inorganic lead halide perovskite solar cells have attracted intensive attention due to the remarkable progress in power conversion efficiency (PCE), increasing rapidly to over 22% in a few years [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. The PCEs of perovskite solar cells with various architectures (mesoporous or planar heterojunction structures) are strongly dependent on the morphology of the perovskite film [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome such challenges, application of pre-synthesized halide perovskite powder as precursor is emerging recently which scores with its higher reproducibility and adaptability of both wet-and dryprocessibility. [82][83][84] Similar to the field of ceramics and metals [85] ; various techniques such as mechanochemical, precipitation, and sonochemical processes can be utilised for the powder synthesis. -FAPbI3 powder was synthesized through a roomtemperature precipitation technique and the PSCs gave higher reproducibility and low trap density along with the improved efficiency was shown as compared to the conventional route.…”
Section: Advanced Perovskite Processing Methodsmentioning
confidence: 99%
“…[124] This is supported by the findings of Zhang et al, who showed that even when using low-grade PbI 2 precursors, precipitated FAPbI 3 or MAPbI 3 powder exhibits a high purity due to a self-cleaning effect in the course of the precipitation process. [41,129] Dou et al investigated the degradation of conventional precursor solutions of triple cation mixed perovskites in DMF, identifying a hydrolysis of DMF with trace water in the solution, thereby forming formic acid (HCOOH) and dimethylamine (DMA). [29] The latter impedes the subsequent crystallization of the perovskite and also leads to a faster degradation of both, thin films and solar cells that were processed from these solutions.…”
Section: Powder Dissolutionmentioning
confidence: 99%